Napovedna vrednost metod za določanje razlike v dolžini spodnjih udov po epifiziodezi - Lunder, Mojca (Medicinski razgledi, 2007)
Background. Limb length discrepancy (LLD) is quite a frequent disorder; it develops in approximately 15% of the population. Lumbar pain is the most common consequence of untreated LLD. Treatment is usually indicated when the condition becomes functionally or esthetically disturbing for the patient. With a simple operation (epiphysiodesis) done before the patient reaches skeletal maturity, LLD can be reduced or equalized. In order to achieve a goodoutcome of epiphysiodesis, it is most important to choose an appropriate time for surgery. Three different methods can be used for this purpose: the Moseley method, the newest multiplier method, and the Menelaus method. The aimof our work was to do an independent clinical verification of all the above-mentioned methods for predicting LLD at skeletal maturity by evaluating the difference in predicted LLD of the authentic multiplier method using the patient's chronological age (MP-KS) and a modified multiplier method using thepatient's skeletal age (MP-SS). Methods. The clinical and radiographic records were reviewed for 43 patients with LLD who have undergone knee epiphysiodesis at the Orthopedic Clinic of the Ljubljana Clinical Centre during the period from 1996 to 2003. Using all four of the above-mentioned methods, LLD was predicted at skeletal maturity. The accuracy, punctionality and interdependence of the used methods were evaluated. To compare each pair of predicted values separately, the Student t-test was used. (Abstract truncated at 2000 characters)
Keywords: Epifize; Leg Length Inequality; Bone Lengthening; Kost, podaljšanje; Kost, razvoj; Methods; Nogi, neenaka dolžina; Epiphyses; noge; Surgery; Bone Development; dolžina; kosti; motnje rasti; epifiziodeza; metode; kirurško zdravljenje; podaljšanje kosti